2023
DOI: 10.1002/app.53671
|View full text |Cite
|
Sign up to set email alerts
|

A strong, biodegradable and transparent cellulose‐based bioplastic stemmed from waste paper

Abstract: It is crucial and significant to boost the utilization of renewable resources and exploitation of biodegradable materials alternative to petrochemical plastics. Waste paper, mainly composed of cellulose (82-95 wt%) and derived from the lignocellulose, is a type of abundant, renewable, and biodegradable resource, whose recycling use and conversion to high value-added products can reduce the pressure on the environment and exert immense economic benefits.Herein, four kinds of common waste paper (e.g., printing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Importantly, the weight of the finished composites increased slightly when compared to the composites without the addition of paper waste. This outcome is in accordance with previous studies that indicated that paper waste provides a good filler material for improving the properties of composite materials, particularly when the density attributes need to be improved [ 22 , 23 , 27 , 47 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, the weight of the finished composites increased slightly when compared to the composites without the addition of paper waste. This outcome is in accordance with previous studies that indicated that paper waste provides a good filler material for improving the properties of composite materials, particularly when the density attributes need to be improved [ 22 , 23 , 27 , 47 ].…”
Section: Resultssupporting
confidence: 92%
“…Moreover, many earlier studies regarding MBC production have also used silica and carbonate sand along with clay to improve the properties of this material [17][18][19][20][21]. In this context, paper waste, which constitutes a significant portion of global solid waste, has become an attractive choice for improving the properties of MBCs because paper waste typically contains cellulose (82-95 wt%), which has an excellent ability to improve the mechanical and physical properties of composite materials [22,23]. Several previous studies have utilized paper waste to improve the qualities of various composite materials because cellulose fibers are known for their high strength and stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Cellulose fibers, possessing numerous advantages such as lightweight, renewable, and biodegradable, are a competitive filler that can enhance the composites performance. [14][15][16] Spray-dried cellulose nanocrystal (SDCNC) particles, a dry form of cellulose-based particles, have shown potential in fabricating PP composites via a cost-effective and solvent-free melt compounding process. [17][18][19][20] Research on developing the SDCNC PP matrix composites with high performance using a melt compounding process attracts interest from academia and industry.…”
Section: Introductionmentioning
confidence: 99%
“…The growing concerns about environmental issues has led to increased interest in incorporating natural fillers, such as wood flour, jute, rice husks, and cellulose fibers, in PP composites 10–13 . Cellulose fibers, possessing numerous advantages such as lightweight, renewable, and biodegradable, are a competitive filler that can enhance the composites performance 14–16 . Spray‐dried cellulose nanocrystal (SDCNC) particles, a dry form of cellulose‐based particles, have shown potential in fabricating PP composites via a cost‐effective and solvent‐free melt compounding process 17–20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, with the growing emphasis on sustainable development and ecological economics, stricter regulations have been imposed regarding the use of petroleum-based raw materials. The growing urgency to explore renewable polymeric materials derived from biomass, such as cellulose [40,41], lignin [42,43], and plant oil [44,45], has become increasingly evident. Among these biomass sources, plant oils have gained significant recognition for their pivotal role in producing functional and sustainable polymeric materials and additives.…”
Section: Introductionmentioning
confidence: 99%